The legal implications of the changing nature of employment in Malaysia / Jashpal Kaur Bhatt - Kaur Bhatt, Jashpal (Faculty of Administratron and Law, 2004)
As we head towards pervasive globalisation, knowledge-economy and electronic commerce, the impact of policies and strategies to meet the new demands of the marketplace on the work force, have far reaching consequences. Not only will the work force have to meet these challenges to traditional forms of employment but the very nature and perception of the employment relationship will have to evolve to cater to and meet the demands of the modern economy of Malaysia. In tandem with these developments will be the requirement for labour or employment laws to keep pace with these changes. This article looks at some of the issues relating to the changes in the nature of employment and the judicial trends in relation to the employment relationship.